Pedagogika dialogu jako odpowiedź na wyzwania współczesnych relacji międzykulturowych .......... 71 - Orzeł-Dereń, Kinga (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
PEDAGOGY OF DIALOGUE AS A RESPONSE TO THE CHALLENGES OF CONTEMPORARY INTERCULTURAL RELATIONSDialogue pedagogy is a response to the challenges posed by the increasing multiculturalism of modern societies. This article aims to analyze the theoretical and practical aspects of dialogue pedagogy in the context of intercultural education. The paper discusses the philosophical foundations of this approach, drawing on the concepts of Martin Buber, Hans-Georg Gadamer, and Paulo Freire, emphasizing the role of dialogue in building interpersonal relationships and developing intercultural competencies. Contemporary educational challenges related to globalization, migration, and intercultural conflicts are also examined. The practical section presents strategies for implementing dialogue pedagogy, highlighting the effectiveness of didactic methods such as Socratic, experiential learning, and intercultural mentoring. The article emphasizes the importance of dialogic education in counteracting stereotypes, fostering social integration, and developing essential skills for functioning in a multicultural society.